2017
DOI: 10.1111/jopy.12309
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescents' Prosocial Behavior Predicts Good Grades Beyond Intelligence and Personality Traits

Abstract: Findings supported the view of PB as a strength and a key resource for adolescents' academic attainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 77 publications
5
45
1
3
Order By: Relevance
“…Adams et al ( 1999 ) found that after accounting for hyperactivity, conduct problems, and emotional problems, neither peer problems nor prosocial behavior related to math achievement test results; however, prosocial behavior remained related to reading achievement test results. This contrasts with Gerbino et al ( 2018 ) results which indicated that prosocial behavior remains a significant correlate of overall grades after accounting for multiple other factors.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Adams et al ( 1999 ) found that after accounting for hyperactivity, conduct problems, and emotional problems, neither peer problems nor prosocial behavior related to math achievement test results; however, prosocial behavior remained related to reading achievement test results. This contrasts with Gerbino et al ( 2018 ) results which indicated that prosocial behavior remains a significant correlate of overall grades after accounting for multiple other factors.…”
Section: Introductioncontrasting
confidence: 90%
“…Wentzel ( 1993 , 1998 ) has repeatedly found a strong link between prosocial behavior and academic achievement. More recently, Gerbino et al ( 2018 ) analyzed data from an Italian large-scale assessment. They demonstrated that prosocial behavior remained a significant predictor of grades even after accounting for other variables such as personality factors and IQ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined above, most research on youth callousness has focused on delinquency, with scant examination of wider health or functional outcomes. On the other hand, low prosocial behavior, as well as being associated with externalizing behaviors (Flynn et al 2015;Nantel-Vivier et al 2014), has also been linked to poor socio-emotional adjustment, including academic underachievement (Caprara et al 2000;Gerbino et al 2017). Of note, persistently high levels of CP predict greater mental and physical health difficulties in adulthood, along with worse education and employment outcomes (Fergusson et al 2005;Moffitt et al 2002;Odgers et al 2007).…”
mentioning
confidence: 99%
“…Associations between EF and prosocial behavior are likely to provide another pathway by which EF can promote school readiness, in that prosocial behavior has been identified as an important predictor of academic achievement (Caprara, Barbaranelli, Pastorelli, Bandura, & Zimbardo, 2000;Gerbino et al, 2017). Different reasons could explain why prosocial children do better in school: greater acceptance from peers that contributes to children's inclusion in group-based learning experiences, greater reciprocal support from peers for solving problems, or teachers' preferences for prosocial children producing higher-quality individualized instruction (Palermo, Hanish, Martin, Fabes, & Reiser, 2007;Wentzel, 1993).…”
mentioning
confidence: 99%